Molecular methods to determine the presence of hepatitis B virus ( HBV ) genotypes in the serum of a hbv-infected chacma baboon - Naicker., Tholsi. Jocelyn. (My University, 2004)
In the course of a previous study (Kedda, et al., 2000), it became evident that the baboons had been inoculated with a mixture of HBV genotypes, namely, genotypes A and non-A. Therefore, a follow up study was undertaken to determine whether either A or non-A HBV genotypes predominated over the other during the time course of 52 weeks post-inoculation of HBV into baboons. HBV DNA extracted from sera obtained from one of the four HBV positive baboons, at two time points during a 52 week post-HBV inoculation period, was amplified using primers specific for the HBV core region that is well conserved in all genotypes.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Chemical Pathology. Johannesburg, 2004
Keywords: Hepatitis B virus; DNA